Knowledge Sharing in an Emerging Industry Cluster: A Saudi Arabian Case Study - Zafer, Aliah Mohammad A (Curtin University, 2017)
This study explored how clustering supports knowledge sharing in an emerging, government-directed industry cluster in the context of Saudi Arabia. It established that lateral actors play a leading facilitative role while the presence of formal, informal mechanisms and personal ties among actors supports cluster knowledge sharing. Limited numbers of vertical and horizontal actors located in the cluster partly account for limited strength and depth of social capital and the lack of trust which impedes knowledge sharing.